Shuttlecock Collector Machine - Ahmad Bakhtiar, Nur Mahirah Madihah; M.Kamal, Nurul Atiqah Aisyah; Nakharuddin, Ahmad Huzaifah; Mohammad Noor, Hafsa (Multidisciplinary Applied Research and Innovation, 2022)
Badminton is a game played on a rectangular court by two players or two pairs of players equipped with light rackets used to volley a shuttlecock over a high net that divide the court in half. Usually, the shuttlecock are easily damaged and would be replaced every three to four games, or sometimes sooner if the played with higher intensity. During training, a lot of shuttlecock were used and burdened the players to pick up all the scattered shuttlecock manually at the end of their training. It requires energy to stack back all the shuttlecock together, but the player is already worn out after the training session. Collecting the shuttlecock manually will sometimes damage the feather on the shuttlecock itself. In this study, a portable and stackable shuttlecock collector machine was fabricated to speed up the time in collecting the shuttlecock and automatically stack in 4 replaceable cylinder tube with diameter 7 cm for 100 shuttlecocks. A barricade was used to make sure that the movement for the shuttlecocks is downward when they enter the cylinder tube and block the shuttlecock if the position is upward. The result for the average time taken of Shuttlecock Collector Machine is 5.1 minutes while the manual method is 8.6 minutes. This shows that Shuttlecock Collector Machine can shorten the process as the manual method require the person that collecting to collect the shuttlecock to bow down as they need to collect the shuttlecock on the floor. The damaged shuttlecock average were only 2 shuttlecocks caused by stuck under the sweeper. From result achieved, this Shuttlecock Collector Machine require 40.7 % less time than manual pick up. The design can be offered by this shuttlecock collector machine, surely it will benefit the badminton players and other related businesses in the future